140k views
4 votes
Select the equivalent expression.

Select the equivalent expression.-example-1

2 Answers

2 votes

Answer:

C

Explanation:

Using the rule of exponents


(a^(m)b^(n)) ^(p) =
a^(mp) ×
a^(np)

Thus


(7^(2)5^(6))^4

=
7^(2.4) ×
5^(6.4)

=
7^(8) ×
5^(24) → C

User Mestre San
by
4.7k points
3 votes

C, because we multiply the exponents to get the answer.

User Florisla
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.